2014
DOI: 10.1186/1471-2393-14-241
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin pathway gene expression in human placenta, amnion and choriodecidua is differentially affected by preterm and term labour and by uterine inflammation

Abstract: BackgroundElucidation of the biochemical pathways involved in activation of preterm and term human labour would facilitate the development of effective management and inform judgements regarding the necessity for preterm tocolysis and post-term induction. Prostaglandins act at all stages of human reproduction, and are potentially activators of labour.MethodsExpression of 15 genes involved in prostaglandin synthesis, transport and degradation was measured by qPCR using tissue samples from human placenta, amnion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 51 publications
3
38
0
1
Order By: Relevance
“…Among other key enzymes of prostaglandin synthesis, PTGES , involved in PGF 2 synthesis, was elevated in the amnion in TIL cases [148]. The same study found increased expression levels of AKR1C3 (aldo-keto reductase), involved in PGF 2α synthesis, in the choriodecidua in TIL cases [148].…”
Section: Discussionmentioning
confidence: 97%
“…Among other key enzymes of prostaglandin synthesis, PTGES , involved in PGF 2 synthesis, was elevated in the amnion in TIL cases [148]. The same study found increased expression levels of AKR1C3 (aldo-keto reductase), involved in PGF 2α synthesis, in the choriodecidua in TIL cases [148].…”
Section: Discussionmentioning
confidence: 97%
“…We demonstrated that the inflammatory marker IL-6 is upregulated in labored placentas, collected from women with vaginal delivery, compared to placentas from women who underwent elective cesarean section. Phillips et al, demonstrated a negative correlation between inflammatory prostaglandins synthetic enzymes expression and the duration of labor in term and preterm gestations, suggesting that transcriptionally regulation of inflammatory related genes affects parturition in terms of prolonged stressful labor (Phillips et al, 2014). In agreement with the hypothesis of an acute and self resolving inflammation characterizing the physiology of labor, we showed that IL-6 cytokine expression inversely correlates with labor duration, ranging from 1 h to 10 h. This observation suggests that a robust inflammatory mediators release facilitates the expulsion of a viable offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Placental expression of 17β-HSD3, which is involved in testosterone formation, is increased in preeclamptic women ( Shao et al, 2017 ). 17β-HSD5 protein ( Phillips et al, 2014 ) and 17β-HSD7 mRNA ( Krazeisen et al, 1999 ) expression were shown in human placenta.…”
Section: Steroid Hormonesmentioning
confidence: 99%